2022
DOI: 10.3390/su14020983
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of International Markets and New Digital Technologies on Business Innovation in Emerging Markets

Abstract: International markets and digital technologies are considered among the factors affecting business innovation. The emergence and deployment of digital technologies in emerging markets increase the innovation potential in businesses. Companies with an entrepreneurial orientation also strengthen their innovation capabilities. The present study aimed to investigate the impact of international markets and new digital technologies on business innovation in emerging markets, and to estimate the mediating effect of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 86 publications
1
47
0
2
Order By: Relevance
“…External competition for businesses has grown stronger, and the market environment has become more diverse in the digital economy era ( Rosenbusch et al, 2013 ). Firms often engage in entrepreneurial activities to ensure their success and survival in highly dynamic and competitive contexts ( Dana et al, 2022 ). The dynamic environment of market competition significantly impacts corporate innovation and entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…External competition for businesses has grown stronger, and the market environment has become more diverse in the digital economy era ( Rosenbusch et al, 2013 ). Firms often engage in entrepreneurial activities to ensure their success and survival in highly dynamic and competitive contexts ( Dana et al, 2022 ). The dynamic environment of market competition significantly impacts corporate innovation and entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, digital transformation has been speeded up by the main technologies of the Fourth Industrial Revolution (4IR) such as artificial intelligence (AI) and autonomous driving. In [6] the research illustrated that international markets and digital technologies are positively related with innovation. Moreover, the digital technologies and international markets will be more involved in mutual relationships.…”
Section: Digital Transformation For Economic Innovationmentioning
confidence: 99%
“…In addition, some scholars have paid attention to the impact of digital technology development on entrepreneurship. Digital technologies can facilitate the development of emerging markets and increase the resilience of social entrepreneurship [24]. ey have explored the mechanism of digital technology and found that innovation ability can be strengthened by the indirect effects of improving entrepreneurs' willingness by using digital skills.…”
Section: Introductionmentioning
confidence: 99%